PENGARUH KOMPETENSI, INDEPENDENSI DAN TEKANAN WAKTU TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN DENGAN SKEPTISME PROFESIONAL SEBAGAI VARIABEL INTERVENING - Fransisco Fransisco; Fransiskus Fransiskus; Indri Indri; Pordinan Pordinan; Rara Rara; Rizqi Rizqi; Zulmanto Zulmanto; Haryono Umar (Lembaga Penelitian Universitas Trisakti, 2019)
The ability to detect fraud is a skill or expertise of the auditor to find indications of the fraud. This research aims to determine the effect of competence, independence and timeo detect fraud. This research was conducted at Jakarta in 2019. The population of this rese rch is a public accounting of big four by spreading questionnaire directly to the Respondents. Respondents in this study were 50 auditors working at big four public accounting firms. Research using primary data, Analysis of the data used is PLS (Partial Least Square). The results of this study indicate that the competency and independency affect the auditor's ability to detect fraud through professional skepticism positively while time pressure affect the auditor's ability to detect fraud through professional skepticism negatively.